The Role of the Philosopher of Education in the Task of Decoloniality - Azada-Palacios, Rowena (Archīum Ateneo, 2023)
This paper explores the meaning of ‘decolonization’ in relation to the school curriculum and the role of the philosopher of education in this task. Taking the Philippines as an example, this paper illustrates how coloniality has underpinned not only school curricula, but also entire systems of formal education in the post-colony. Following from this, it argues that decolonization in education must transcend the diversification of curricula and aim at a broader vision of justice. Drawing from the author’s own attempts to reimagine the teaching of national identity, the paper proposes that philosophers of education who wish to participate in the work of decoloniality view their contribution as the three-fold task of historical critique, conceptual retrieval, and creative reimagination.